Based on the Wavelet Function of Power Network Fault Location - Fan YU; Shuo ZHANG; BaoLong Liu (Institute of Advanced Engineering and Science, 2013)
In order to improve the measurement accuracy, in the traditional measuring method based on, by avoiding wave speed influence on fault location of transmission line method, and compares it with the combination of wavelet transform. This article selects dBN wavelet and three B spline wavelet contrast, compared them with new methods, through the Xi'an City Power Supply Bureau of the actual fault data validation. The results show that, with3 B spline wavelet and the new method combined with the location results are closer to the actual distance, its accuracy is higher than that of db3wavelet transform and a new method derived from the results, the error is far less than the db3 wavelet function, location is satisfactory. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2363